Paternal retraction of a fragile X allele to normal size, showing normal function over two generations. Issue 1 (21st September 2021) - Bartlett, Essra; Archibald, Alison D.; Francis, David; Ling, Ling; Thomas, Rob; Chandler, Gabrielle; Ward, Lisa; O'Farrell, Gemma; Pandelache, Alison; Delatycki, Martin B.; Bennetts, Bruce H.; Ho, Gladys; et al.
Abstract: The FMR1 premutation (PM:55‐199 CGG) is associated with fragile X‐associated tremor/ataxia syndrome (FXTAS) and when maternally transmitted is at risk of expansion to a hypermethylated full mutation (FM: ≥ 200 CGG) that causes fragile X syndrome (FXS). We describe a maternally transmitted PM (77 CGG) that was passed to a son (103 CGG), and to a daughter (220–1822 CGG), who were affected with FXTAS and FXS, respectively. The male with the PM showed low‐level mosaicism for normal size of 30 and 37 CGG. This male had two offspring: one female mosaic for PM and FM (56, 157, >200 CGG) and another with only a 37 CGG allele detected in multiple tissues, neither with a clinical phenotype. The female with the 37 CGG allele showed normal levels of FMR1 methylation and mRNA and passed this 37 CGG allele to one of her daughters, who was also unaffected. These findings show that post‐zygotic paternal retraction can lead to low‐level mosaicism for normal size alleles, with these normal alleles being functional when passed over two generations.